2016
DOI: 10.1088/1674-1056/25/9/097402
|View full text |Cite
|
Sign up to set email alerts
|

Observation of selective surface element substitution in FeTe 0.5 Se 0.5 superconductor thin film exposed to ambient air by synchrotron radiation spectroscopy

Abstract: A systematic investigation of oxidation on a superconductive FeTe 0.5 Se 0.5 thin film, which was grown on Nb-doped SrTiO 3 (001) by pulsed laser deposition, has been carried out. The sample was exposed to ambient air for one month for oxidation. Macroscopically, the exposed specimen lost its superconductivity due to oxidation. The specimen was subjected to in situ synchrotron radiation photoelectron spectroscopy (PES) and x-ray absorption spectroscopy (XAS) measurements following cycles of annealing and argon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Using the photoelectron emission spectroscopy and X‐ray absorption spectroscopy, the authors of another study [ 11 ] found the loss of chalcogens by FeTe 0.5 Se 0.5 film, and in the film of 100 nm thickness, the irreversible changes occurred over a period of 1 month. Increasing the temperature can significantly speed up this process.…”
Section: Resultsmentioning
confidence: 99%
“…Using the photoelectron emission spectroscopy and X‐ray absorption spectroscopy, the authors of another study [ 11 ] found the loss of chalcogens by FeTe 0.5 Se 0.5 film, and in the film of 100 nm thickness, the irreversible changes occurred over a period of 1 month. Increasing the temperature can significantly speed up this process.…”
Section: Resultsmentioning
confidence: 99%